Dampak Kenaikan Tarif Dasar Listrik Terhadap Institusi Rumah Tangga di Indonesia dengan Model Computable General Equilibrium - Yuki Tiara Wiharja; Christine Natalia (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2013)
Electricity price has risen for 10% every year in average . The reason for making the price rising is to reducethe electricity subsidy that been given by PLN as the main distributor of electricity in Indonesia. The aim ofreducing the subsidy is increase the process of electricity equalization among other remote regions inIndonesia. In 2008, Indonesian Bureau of Statistics (BPS) noted that household institutions absorbed around50% of national electricity consumption. For that reason, household institutions were in the first place as thehighest user of electricity, while industrial sectors were in the second place. Computable GeneralEquilibrium (CGE) is a mathematical model that formulates the general equilibrium problems. CGE modelwas started from the economy theory, economic mathematic, and computation theory. Formulation of CGEmodel will be further analyzed by the aid of software called GAMS. GAMS is a software developed by GAMSDevelopment Corporation. GAMS is the first software that using an algebraic modeling language for itsinput. By using a CGE method. It is expected to give a picture of the impact in implementing a new policyrelated to the rising price of electricity. After the simulation process, the result showed that the rising ofelectricity price affect other commodities price.